Optimasi Pencarian Kata pada Aplikasi Penerjemah Bahasa Mandarin – Indonesia Berbasis Android dengan Algoritma Levenshtein Distance - Peggy Peggy; Seng Hansun (Ultima Computing : Jurnal Sistem Komputer, 2015)
In the Chinese-Indonesian language translator application on electronic device, such as Android, input is all about pinyin. Sometimes, some errors could occured. User can not find the word which he is searching for. These errors can increase the number of processing time. A solution to solve these errors is performing optimization on the application, i.e. by providing some alternative approaches word which typed by user. Application will sort alternative words according to the smallest distance to the largest distance. Then, application will display alternative words order from top priority which has the smallest distance, to low priority which has the largest distance. In brief, translator application with optimization is useful to shorten processing time of translating from Chinese to Indonesian by providing alternative words. Optimization is done with Levenshtein Distance algorithm. Levenshtein Distance algorithm will calculate the difference between the distance of the word user typed among alternative words. Index Terms─Android, Chinese, Indonesian, Levenshtein Distance, optimization, translator application